Geoeffectiveness Prediction of CMEs - Besliu-Ionescu, Diana; Mierla, Marilena (Frontiers in Astronomy and Space Sciences, 2021)
Coronal mass ejections (CMEs), the most important pieces of the puzzle that drives space weather, are continuously studied for their geomagnetic impact. We present here an update of a logistic regression method (Besliu-Ionescu et al., 2019) based on Srivastava (2005) model, that attempts to forecast if a CME will be associated with a geomagnetic storm defined by a minimum Dst value smaller than -30 nT. The model is run for a selection of CMEs listed in the LASCO catalogue during the solar cycle 24. It is trained on three fourths of these events and validated for the remaining one fourth. Based on five CME properties (the speed at 20 solar radii, the angular width, the acceleration, the measured position angle and the source position – bin-type variable) the model successfully predicted 0.98 of the events from the training set, and 0.98 of the events from the validation one.